Molecular dynamics-guided modification of AFPIV 3D structure to improve ice binding interaction - Eskandari, Azadeh Hassan (2023)
Exotic properties of antifreeze proteins (AFPs) and antifreeze peptides have currently been widely used in cryopreservation due to their special functions; ice crystal growth inhibition (IRI) and thermal hysteresis (TH). Chemical synthesis of AFPs and their natural protein (wild-type) are uneconomical and time consuming. Moreover, some AFPs have low function naturally (less activity) to be used in cryopreservation where the cells can be damaged due to formation of ice crystals and toxicity of cryoprotectants. Thus, this study aims to design a new AFP from the wild-type with improved activity using molecular dynamics (MD)guidance. In this in-silico study, the modified afp1m from yeast was fusedto multi-helices of AFPIV from fish. A new linker was designed to boost the iceinteraction of AFPIV and make it more cost-effective. The newly designed modelwas designated as AFP1m3. The present of the new linker has improved theinteraction between the ice lattice and AFP1m3, thus make it more economicalfor further practical utilizations. Various bioinformatics tools such as ExpasyProtparam, PepWheel, SWISS-MODEL, Phyre2, ERRAT, PROCHECK andProQ were used to analyze the physicochemical, functional and structuralproperties of this newly designed AFP (AFP1m3) model. Furthermore, MDsimulation with GROMACS software for 100 ns, was conducted to evaluate theinteraction between ice and the new mutant. The primary structure analysisshowed that AFP1m3 is hydrophobic in nature due to the high content of non-polar residues. The secondary structure analysis revealed that this protein wasfully helix by using PepWheel tool. The results of the 3D structure model byexcluding SWISS-MODEL and Phyre2 demonestrated that AFP1m3 had thebest model by these modelling tools with QMEAN of -0.23, confidence of 98.2%and coverage score of 23% as well as Ramachandran value of around 96%, hadthe best model. In addition, the analysis of the predicted model validity provedthat AFP1m3 was extremely a good model according to ProQ tool criteria.Analysis of MD simulation results illustrated that AFP1m3 had more rigidityaccording to its proper helical structure, better interaction with ice due to its stability of hydrogen bonds which mimic the freezing and thawing temperatures in cryopreservation condition at -8 and 25 ºC and high activity regarding to the low rate of ice growth at three different temperatures. This study may shed light on application of newly designed AFPIV in cryopreservation at low concentration. The conclusion can be drawn that the AFP1m3 improved its anti-freeze properties with better ice interaction (high activity) at a lower cost to meet medical applications especially in cryopreservation of cells and tissues.